Design and Validation of a PLC-Based Smart Solar Dome Dryer as a Contextual Learning Platform for Enhancing Industrial Competencies in Informatics Education - Baso Ali; Muhammad ikram; Shoira Abdiyeva (Jurusan Teknik Informatika dan Komputer, 2026)
Purpose - Industry 4.0 increases competency demands for informatics graduates. Graduates need software skills and industrial automation literacy. This study designed and validated a Programmable Logic Controller (PLC)-based smart solar dome dryer as a contextual learning platform for developing industrial competencies in informatics education. Design/methods/approach – This study designed and validated a PLC-based smart solar dome dryer as a contextual learning platform to enhance students’ industrial competencies. The prototype was assessed through functional testing, sensor accuracy and stability testing, drying performance evaluation, and expert feasibility review as a learning medium. Learning effectiveness was examined using a quasi-experimental pretest–posttest design with 120 informatics students in experimental and control groups. Instrument validity and reliability were confirmed using Aiken’s V and Cronbach’s alpha. Findings – The system operated reliably as a closed drying platform and produced more stable temperature and humidity conditions with more efficient drying time than conventional methods. Students in the experimental group achieved significantly higher competency gains than those in the control group (p < 0.001), with a very large effect size (Cohen’s d = 3.21; Hedges’ g = 3.18). Research implications/limitations – The findings suggest that authentic PLC-based automation systems can support contextual industrial learning in Education 4.0. However, the quasi-experimental design and single institutional context limit causal and generalization claims. Originality/value – This study contributes a validated agro-industrial automation prototype and empirical evidence on its potential value as a contextual learning platform in informatics education.